Serum metalloproteinases 1 and 7 in the diagnosis of idiopathic pulmonary fibrosis and other interstitial pneumonias - Morais, A (2015)
INTRODUCTION: Accurate diagnosis of idiopathic pulmonary fibrosis (IPF) has important therapeutic and prognostic implications and would be greatly aided by reliable diagnostic biomarkers as IPF has sometimes overlapping features with other interstitial lung diseases (ILD). OBJECTIVES: To explore the value of serum metalloproteinases (MMP) 1 and 7 levels in the differential diagnosis of IPF with other ILD. METHODS: MMP-1/7 serum levels were measured using Luminex xMAP technology in 139 patients- 47 IPF, 36 non-IPF Usual Interstitial Pneumonia (UIP), 14 idiopathic Nonspecific Interstitial Pneumonia (iNSIP), 29 secondary NSIP (secNSIP), 13 stage IV sarcoidosis- and 20 healthy controls, and compared using the Mann-Whitney U test. RESULTS: MMP-1 was significantly higher in IPF than non-IPF UIP (P = .042) and sarcoidosis (P = .027). MMP-7 was significantly higher in IPF than controls (P < .001), non-IPF UIP (P = .003), secNSIP (P < .001), and sarcoidosis (P < .001). The Area Under the Curve for IPF versus other ILD was 0.63 (95%CI, 0.53-0.73) for MMP-1, 0.73 (95%CI, 0.65-0.81) for MMP-7, and 0.74 (95%CI, 0.66-0.82) for MMP-1/MMP-7 combined. Sensitivity and specificity for MMP-7 cutoff = 3.91 ng/mL was 72.3% and 66.3%, respectively, Positive Predictive Values = 52.3% and Negative Predictive Values = 82.4%. CONCLUSIONS: MMP-1 and particularly MMP-7 serum levels were significantly higher in IPF than in non-IPF UIP, the main entity in differential diagnosis. The value of these biomarkers as additional tools in a multidisciplinary approach to IPF diagnosis needs to be considered and further explored.